Kinetic changes associated with extended knee landings following anterior cruciate ligament reconstruction in females. (November 2021) - Larson, Daniel; Nathan Vannatta, C.; Rutherford, Drew; Kernozek, Thomas W.
Abstract: Objectives: To determine the relationship between knee flexion excursion symmetry and lower extremity kinematics, kinetics, and muscle, joint, and ligament forces in females 1–3 years after ACL reconstruction. Design: Cross-sectional. Setting: Laboratory. Participants: Twenty-one, college-aged females. Main outcome measures: Lower extremity kinetics and kinematics, including estimated muscle, tibiofemoral, and ligament forces were assessed using 3D motion analysis and a musculoskeletal modeling approach. Participants demonstrating greater than 10% asymmetry in knee flexion excursion were classified as landing with an "extended knee". Group and between-limb differences were compared. Results: Ten participants were classified as landing with an "extended knee" on the involved limb, while eleven exhibited a symmetric landing pattern. Participants landing with an "extended knee" demonstrated reduced knee extension moment and quadriceps force in the involved limb (p < 0.05). Conclusions: These findings indicate that an "extended knee" landing pattern was associated with reduced knee extension moment and quadriceps muscle force in females 1–3 years after ACL reconstruction. This may represent an altered strategy that clinicians may choose to identify and address during rehabilitation. Highlights: Deficits in landing performance can persist up to three years following ACLR. An "extended knee" landing may be a strategy associated with reduced quadriceps force. This landing strategy may have implications to second ACL injury and osteoarthritis.